2021
DOI: 10.1093/plcell/koab140
|View full text |Cite
|
Sign up to set email alerts
|

Under siege: virus control in plant meristems and progeny

Abstract: In the arms race between plants and viruses, two frontiers have been utilized for decades to combat viral infections in agriculture. First, many pathogenic viruses are excluded from plant meristems, which allows the regeneration of virus-free plant material by tissue culture. Second, vertical transmission of viruses to the host progeny is often inefficient, thereby reducing the danger of viral transmission through seeds. Numerous reports point to the existence of tightly linked meristematic and transgeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 130 publications
0
45
0
Order By: Relevance
“…In addition to plant factors, viral factors can also have a role in allowing a virus to access the meristem. For example, viral suppressors of RNA silencing (VSR) are capable of overcoming antiviral barriers in the SAM ( Bradamante et al, 2021 ), and could be adopted from known seed transmissible viruses to existing systems to facilitate germline mutations. In BSMV and TRV, VSRs have been identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to plant factors, viral factors can also have a role in allowing a virus to access the meristem. For example, viral suppressors of RNA silencing (VSR) are capable of overcoming antiviral barriers in the SAM ( Bradamante et al, 2021 ), and could be adopted from known seed transmissible viruses to existing systems to facilitate germline mutations. In BSMV and TRV, VSRs have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…In BSMV and TRV, VSRs have been identified. The BSMV γb protein mediates vertical transmission, and the 16K protein from TRV is involved in meristem invasion, ultimately resulting in seed transmissibility ( Bradamante et al, 2021 ). The SAM utilizes several defense mechanisms to preclude viral invasion including the expression of resistance genes, autophagy, and RNA interference ( Bradamante et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptomless infection, low titre, and tenacity in the cytoplasm of meristematic cells after heat treatment suggest that SPPV is a persistent virus causing latent infection in sweet potato (Bradamante et al, 2021;Kreuze et al, 2020;Roossinck, 2012;Takahashi et al, 2019). The SPPV-sweet potato relationship is possibly symbiotic because the virus is "allowed" to invade seeds and meristematic cells of sweet potato (Kreuze et al, 2020;Roossinck, 2008Roossinck, , 2012Takahashi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…TRV is a member of the Tobravirus genus, whose genomes consist of bipartite positive-strand RNAs and can infect over 400 plant species. Its wide range of hosts, together with systemic virus movement to all plant tissues including the germline and meristematic tissue, suggested that TRV might be a useful viral vector for genome engineering ( Bradamante et al, 2021 ). Indeed, the transient expression of the TRV-based vector in jasmine tobacco ( N. alata ) delivered meganuclease to the dihydroflavonol 4-reductase ( DFR ) gene and introduced mutations at the desired target site in reproductive organs such as pollen grains with low frequency ( Honig et al, 2015 ).…”
Section: Virus-induced Plant Genome Editingmentioning
confidence: 99%